Determinación del incremento medio anual (ima) e índice de sitio de diferentes especies forestales en el bosque protector prosperina-ESPOL - Jiménez, E. (2010)
In the present study they installed permanent plots of growth (PPC) in a mixed plantation of 10 years in the Protective Forest Prosperina in the campus “Ing. Gustavo Galindo V” located in Guayaquil in the Km 30.5 of the route Perimetral The test was established in an area of 15 has approximately, initially three sites were defined bearing in mind the quality of soil, Good, Intermediate and Bad, across the sampling at random for site there established themselves a total of 7 PPC with an area 1000m2 each one. In every plot there took information of Geographical location and such dasonométrics variables as species, diameter at a height of the breast (DAP), total height. In addition at random a plot was selected by site to realize calicatas where there decided the parameters of texture of soil. With the gathered information the most representative species were selected to determine the volume, basal area, average annual increase (IMA), and index of site for species. I realize a test student “t" to observe if there are significant differences between the qualities of soil evaluating the variables volume and height, finally an analysis multichanged to observe as the chemical elements they influence in the growth of the species. The most representative species were Amarillo, Fernán Sanchez, Leucaena, Neem and Samán, 5 species added 73.8% of the total of individuals, the species with major IMA of height (m), basal area (m2) and volume (m3) is the Samán 0,78 m, 0,0018 m2 and 1,83 m3 respectively followed by Leucaena and Amarillo. The chemical elements Nitrogen (N), Phosphorus (P), Potassium (K), Calcium (Ca) and Boron (B) are those who influence the growth of the mixed plantation.